Peran Strategis Chief Business Officer dalam Pengambilan Keputusan dan Dampaknya Terhadap Efektivitas Bisnis PT Tourezia Cakra Inspira - Muhammad Husnu Riyadhi; Muhammad Bakr Muhlison (Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze the strategic role of the Chief Business Officer (CBO) in decision-making and its impact on operational effectiveness at PT Tourezia Cakra Inspira. This research uses a qualitative approach with a case study method, using data collection techniques such as in-depth interviews, participant observation, and documentation with informants directly involved in the company's work processes. The results indicate that the CBO plays a very dominant role not only at the strategic level but also in daily technical and operational decisions. This situation creates a high degree of decision centralization, which creates bottlenecks in the workflow, slows the approval process, reduces the speed of execution, and reduces the latitude for line managers to make independent decisions. On the other hand, while this centralization helps maintain control and decision accuracy, it is not balanced with the operational demands of service companies that require rapid and flexible responses. This study concludes that a company's operational effectiveness will be more optimal if there is a more structured system of delegation of authority, a clearer division of roles, and strengthened capacity of middle management so that work processes can run more efficiently without compromising the company's strategic direction.